Adsorption of Acacia Bark (Acacia crassicarpa) on Cd(II) Metal in Solution - Mukhlis, Mukhlis; Aulia, Fiona; Tamboesai, Emrizal Mahidin; Devi, Silvera; Perdana, Fitra; Fawrin, Heralda (Journal of The Indonesian Society of Integrated Chemistry, 2026)
Adsorption of Cd(II) metal from aqueous solution using acacia bark powder as adsorbent was performed in this study. This study aims to determine the efficiency and the best adsorption capacity of Acacia bark powder in Cd(II) adsorption with adsorbent dosage and pH parameters. The method used in this study is Cd adsorption (II) batch. Acacia bark powder was characterized using SEM, FTIR and BET to determine surface morphology, powder functional group, powder surface area, pore volume and pore size. Based on research that has been done the best dosage conditions and PH optimization obtained at 3.5 g, pH 8 and adsorption efficiency reached 98.81% and a capacity of 1.3763 mg/g. It is believed that the Acacia bark powder (Acacia crassicarpa) has a high ability to adsorb Cd(II) metal at dose and pH variations